Ibadah sebagai Sistem Pembinaan Manusia: Integrasi Aqidah, Akhlak, Relasi Sosial, dan Kesehatan Mental - Siti Nurhaliza Febryna Khaidir; St Nurul Latifah; Dahlan Lama Bawa (ALSYS, 2026)
In Islam, ibadah (worship) is understood not only as a spiritual obligation but also as a means of holistic human development oriented toward the formation of noble character. This study employs a literature review design by examining reputable scholarly publications from the last ten years drawn from various academic databases. The review focuses on empirical and theoretical studies on core Islamic acts of worship, such as shalat (prayer), fasting, zakat (almsgiving), and other forms of social worship, as well as their impact on strengthening faith, character formation, social relations, and mental health. The purpose of this study is to systematically analyze the role of ibadah as a holistic system of human development that integrates the dimensions of aqidah (creed), akhlak (morality), social relations, and mental health. The findings indicate that worship practices performed consistently and accompanied by spiritual awareness make a significant contribution to the formation of noble character traits, such as honesty, patience, empathy, and self-control. Worship also serves to strengthen individual spirituality and belief, enhance solidarity and emotional support within the community, and promote mental health through reflection, self-awareness, and meaning-making embedded in worship, thereby reinforcing psychological resilience and emotional stability. The study concludes that ibadah in Islam functions as a holistic and integrative system of human development in which the strengthening of aqidah, the formation of akhlak, the cultivation of social relations, and the maintenance of mental health are closely interrelated. The implications of this research suggest that a comprehensive understanding of worship can serve as a foundation for developing moral education, character-building programs, the strengthening of social relations, and mental health interventions based on Islamic spiritual values, while also opening avenues for further research on the integrative mechanisms of worship in character formation through empirical and contextual approaches.